The effect of two sessions of combined jump and sprint training per week on fitness parameters in soccer players. A randomized controlled trial - Bianchi, Mattia; Anderson, Liam; Brownlee, Thomas; Bossi, Lorenzo; Beato, Marco (Biology of Sport, 2023)
This study aimed to investigate the effect of a combined jump and sprint training program, two sessions a week for 6 weeks, on sprinting, change of directions (COD) and jumping performance in semiprofessional soccer players. Twenty soccer players were enrolled in this randomized controlled trial (age 20±2 years, body mass 74.3±5.9 kg). Players were randomized into two groups such as training group (TG, n = 10 players) or control group (CG, n = 10 players). Physical tests were performed before and after 6 weeks of training such as sprint 10 m, sprint 30 m, 505-COD test and standing long jump (LJ). The two groups performed the same training except for the combined jump and sprint training performed twice a week by TG. After 6 weeks of training, between-group analysis reported statistical difference in favor of the TG in sprint 10 m (p = 0.015, η 2 = 0.295, large), sprint 30 m (p < 0.001, η 2 = 0.599, large), in 505-COD (p = 0.026, η 2 = 0.154, large), and LJ (p = 0.025, η 2 = 0.027, small). These data indicate that combined sprint and jump training, when performed twice a week, for the duration of 6 weeks, in addition to the regular team training, can improve specific physical performance in male soccer players. This study has shown that a volume increment of 10% after 3 weeks of training can be a suitable training dose progression and that a combination of 64–70 jumps and 675–738 m of sprinting training per session can yield benefits in sprint, COD and jump performance.